Senam Prolanis Menurunkan Tekanan Darah Lansia Penderita Hipertensi - Adha Reza Fahlevi; Agung Riyadi; Mardiani Mardiani (Poltekkes Kemenkes Bengkulu, 2019)
Hypertension is the cause of death of about 12.8% of total deaths in the world. Based on data obtained from Talang Tinggi Public Health Center in 2017 the number of elderly people with hypertension reached 223 people, one of the handling that can control blood pressure is gymnastics. The purpose of this research was to determine the effect of Prolanis gymnastics (Chronic Disease Management Program) to blood pressure elderly patients with hypertension.This research was an analytic study with quasi experiment. The sample was a mild hypertension patient with age ≥ 60 years old, amounting to 34 people consisting of 17 people in the intervention group and 17 people in the control group. The sampling technique was simple random sampling. Data analysis was used wilcoxon and mann-whitney test.The results of this study showed that there was an effect between Prolanis gymnastics on decline blood pressure of elderly hypertension patients in the intervention group before and after Prolanis gymnastics with p value of systolic blood pressure (p=0.001), p value of diastolic blood pressure (p=0.001). Prolanis gymnastics beneficial for elderly people with hypertension to control and manage the disease experienced. Prolanis gymnastics is expected to be active as a hypertension control program.